Rural Environmental Teaching in Basic General Education - Martínez Pacheco, Martha Isabel (2013)
This paper, based on the Nicaraguan and Belizean contexts, points out the need of providing environmental education to students from the 1st to 6th grades of the Basic General Education to ensure that young generations will live in harmony with nature, which will depend on their healthy practices to protect the planet. For this, we attempt to stimulate the interest of teachers to create environmental teaching/learning strategies in an organized, planned, conscious way to raise students’ awareness and love for their culture and community, and for students to aspire to livein healthy homes. This way, students will succeed in the coexistence experience, in the material and spiritual cultures, and in the economic and development areas.